Effect of drip fertigation on productivity and profitability of castor (Ricinus communis L.): EFFECT OF DRIP FERTIGATION ON PRODUCTIVITY AND PROFITABILITY OF CASTOR - P M VAGHASIA; R L DAVARIYA; K L DOBARIYA (Journal of Oilseeds Research, 2018)
A field experiment was conducted at the Main Oilseeds Research Station, Junagadh Agricultural University, Junagadh (Gujarat) during kharif for three consecutive seasons of the year 2013-14, 2014-15 and 2015-16. The experiment was laid out in randomized block design, with four replications. The soil was medium black in texture. The seven treatments comprised oftwo levels of drip irrigation [at 0.6 and 0.8 Pan Evaporation Fraction (PEF)] with combination of three levels of nitrogen (50 %, 75 % and 100 % of recommended dose through fertigation) and check basin method of irrigation 0.6 IW/CPE ratio with IWof 50 mm. Drip system(4 LPH) was operated after every third day for 2 hours during October and for 1 hour and 45 minutes during November to January. The pooled analysis of results revealed that drip fertigation at 0.8 PEF in conjunction with nitrogen fertigation @ 90 kg/ha in the form of urea (20 kg as basal and 70kg in five equal split doses at 12 days interval) resulted in the highest seed yield (3541 kg/ha), net returns (Rs. 90712/ha) and B:C ratio (3.25). Drip fertigation also recorded saving of 25% nitrogen fertilizer and better water use efficiency. The highest water use efficiency of 12.26 kg/ha mmwas obtained under drip fertigation at 0.6 PEF +100% RDN (T3).